Investigating empathy in interpreter-mediated simulated consultations: An explorative study. Issue 1 (January 2018) - Krystallidou, Demi; Remael, Aline; de Boe, Esther; Hendrickx, Kristin; Tsakitzidis, Giannoula; van de Geuchte, Sofie; Pype, Peter
Highlights: Interpreters affect meaning and/or intensity of patients' empathic opportunities. This effect is accompanied by changes in doctors' empathic responses. Communication curricula should consider the interpreter's effect on empathy. Abstract: Objective: To explore i) the ways in which empathic communication is expressed in interpreter-mediated consultations; ii) the interpreter's effect on the expression of empathic communication. Methods: We coded 9 video-recorded interpreter-mediated simulated consultations by using the Empathic Communication Coding System (ECCS) which we used for each interaction during interpreter-mediated consultations. We compared patients' empathic opportunities and doctors' responses as expressed by the patients and doctors and as rendered by the interpreters. Results: In 44 of the 70 empathic opportunities there was a match between the empathic opportunities as expressed by the patients and as rendered by the interpreters. In 26 of the 70 empathic opportunities, we identified 5 shift categories (reduced emotion, omitted emotion, emotion transformed into challenge, increased challenge/progress, twisted challenge) in the interpreter's rendition to the doctor. These were accompanied by changes in the level of empathy and in the content of the doctors' empathic responses. Conclusion: The interpreters' renditions had an impact on the patients' empathic opportunities and on the doctors' empathic responses in one third of the coded interactions. Practice implications: Curricula with a focus on intercultural communication and/or empathy should consider the complexity of interpreter-mediated interaction and the interpreter's impact on the co-construction of empathy.